2020
DOI: 10.1111/add.15114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of screening, brief intervention and referral to treatment for unhealthy alcohol and other drug use in mental health treatment settings: a randomized controlled trial

Abstract: Aims To test the efficacy of a brief intervention to reduce alcohol or drug use and to promote use of addiction services among patients seeking mental health treatment. Design and setting A multi‐centre, longitudinal, two‐group randomized controlled trial with randomization within each of two mental health treatment systems located in Ventura County and Los Angeles County in California, USA. Participants A total of 718 patients (49.2% female) aged 18 and older with a mental health diagnosis and either a heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…An important future direction is therefore to examine which intervention techniques are most effective, to improve CU treatments. Karno et al (2020) found positive effects of the Screening, Brief Intervention, and Referral to Treatment upon reduction of alcohol and other substance use, but not for CU. These findings suggest that CU treatment may need to be more targeted, and specifically that a focus on CU and the inclusion of MI, CBT and MET strategies is likely to be of benefit (Gates et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An important future direction is therefore to examine which intervention techniques are most effective, to improve CU treatments. Karno et al (2020) found positive effects of the Screening, Brief Intervention, and Referral to Treatment upon reduction of alcohol and other substance use, but not for CU. These findings suggest that CU treatment may need to be more targeted, and specifically that a focus on CU and the inclusion of MI, CBT and MET strategies is likely to be of benefit (Gates et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Future research in this area should seek to understand BT as practiced among a larger sample of different provider types, as well as patients’ direct experiences and perspectives. Regardless of research needs, the BT practice variations and relatively weak internal standards identified lend support issues raised in prior research [ 12 , 13 , 32 ], thus reinforcing the need for more consistent implementation and quality assurance guidelines in FQHCs and other settings where BT is implemented. Finally, the importance of a client’s stage of change for determining BT appropriateness and content suggests the use of standardized assessments could be employed to guide clinical decision making in this area (see [ 51 ]).…”
Section: Discussionmentioning
confidence: 87%
“…Yet, other research has provided no clear example of how BT was operationalized or simply accepted that it was delivered when reported so by service providers [4,[25][26][27][28][29][30][31]. This inconsistent operationalization combined with a noted lack of fidelity measurement [32] in prior BT research raise validity and reliability concerns that hamper the quality of evidence on the intervention's efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…22 A RCT conducted on 718 individuals comparing brief interventions including motivation interviewing and health informational care sessions found both of them effective at reducing frequency or abstinence of heavy drinking and stimulant use but had no effect on cannabis use. 23 Anderson et al established that primary care training and support in alcohol screening and brief advice had an impactful effect on patients who received the intervention that was sustained even after 9 months. 24 This study also showed that early and brief interventions at the level of filter clinics or emergency departments can be helpful in reducing substance use disorders.…”
Section: Resultsmentioning
confidence: 99%